Does trade integration alter monetary policy transmission? - Tobias J. Cwik; Gernot J. Müller; Maik H. Wolters (Goethe University Frankfurt, Center for Financial Studies (CFS), 2008)
This paper explores the role of trade integrationor opennessfor monetary policy transmission in a medium-scale New Keynesian model. Allowing for strategic complementarities in price-setting, we highlight a new dimension of the exchange rate channel by which monetary policy directly impacts domestic inflation. Although the strength of this effect increases with economic openness, it also requires that import prices respond to exchange rate changes. In this case domestic producers find it optimal to adjust their prices to exchange rate changes which alter the domestic currency price of their foreign competitors. We pin down key parameters of the model by matching impulse responses obtained from a vector autoregression on U.S. time series relative to an aggregate of industrialized countries. While we find evidence for strong complementarities, exchange rate pass-through is limited. Openness has therefore little bearing on monetary transmission in the estimated model.
urn:nbn:de:hebis:30-57676
Keywords: F41; F42; E52; 330; Monetary Policy Transmission; Open Economy; Trade Integration; Exchange Rate Channel; Strategic Complementarity; Exchange Rate Pass-Through; Transmissionsmechanismus; Exchange Rate Pass-Through; Offene Volkswirtschaft; Ungleichgewichtstheorie; Theorie